(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Democracy is one of the West’s most important contributions to universal human heritage. Still it presents some drawbacks in the ways it relates to certain global problems, especially climate change. In this paper we claim that these drawbacks can be ameliorated by turning to a non-Western tradition, specifically to Confucianism. A tradition that, first of all, we will have to analyze in its proper terms – i.e. in ideographical ones –, in order to relate it, afterwards, to democracy in what concerns climate change. Finally, we will propose a synthesis – what we call 君人, individual and king –, introducing in the concept of democracy the idea of harmony between nature and society. In other terms, we will defend a royal/real democracy, in which the political subject would be individual 人and king 君at the same time.